2013
DOI: 10.1002/chem.201300507
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalyzed Synthesis of Iodofulvenes

Abstract: We report the gold-catalyzed synthesis of highly functionalized iodofulvenes from iododialkynes under mild conditions. The catalytic cycle involves the formation of gold acetylides and vinylgold intermediates. These intermediates can then undergo an unprecedented iodine/gold exchange. This new pathway for catalyst transfer in dual gold catalysis opens up the possibility of highly regioselective transformations directed by the gold in the organogold intermediates. The resulting products are well suited for furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(37 citation statements)
references
References 53 publications
0
37
0
Order By: Relevance
“…129 It is interesting that, in contrast to that found in the reactions between alkynes and alkenes, these types of diyne cyclizations are smoothly catalysed with σ,π-digold( i ) alkyne complexes. 129131 …”
Section: Digold Complexesmentioning
confidence: 99%
“…129 It is interesting that, in contrast to that found in the reactions between alkynes and alkenes, these types of diyne cyclizations are smoothly catalysed with σ,π-digold( i ) alkyne complexes. 129131 …”
Section: Digold Complexesmentioning
confidence: 99%
“…Gold catalysis has emerged as ah ighly active field in homogenous catalysis in recent decades. [1] Recently, Zhang's group and our group independently discovered an ew reactivity pattern for gold-catalyzedr eactions, in the course of the studies onto the activation of diynes, [2,3] which was entitled"dual activation". This termw as first introduced by To stee tal.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have provided strong evidence for their existence, and have demonstrated their powerful reactivity [5155], identifying them as key players in ongoing activity developing the exciting notion of dual activation using gold catalysts [56]. …”
Section: Resultsmentioning
confidence: 99%